Relations between Islamic Fiqh and Politics in Indonesia - Muhammad Asrul Maulana (Jurusan Hukum Tata Negara Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
Islamic Jurisprudence is a system of laws and principles that govern human life in the Islamic religion. In Indonesia, Islamic Fiqh has long been involved in the political arena, especially in law making and political decision making. This article aims to explore the relationship between Islamic Jurisprudence and politics in Indonesia, and its implications for political decision-making in the country. The method used in this research is literature study and literature review. The results of the research show that Islamic Fiqh has long been involved in the political arena in Indonesia, both in making laws and in making political decisions. However, the relationship between Islamic Jurisprudence and politics in Indonesia is not always harmonious. especially in the context of differences of opinion between various groups or schools of thought in Islam. This study provides important implications for political decision-making in Indonesia, particularly in efforts to harmonize the principles of Islamic Jurisprudence with democratic norms and principles.